2015
DOI: 10.1021/mp500841w
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-Mediated Down-Regulation of the Multidrug-Resistance Protein BCRP/ABCG2 in Porcine and Human Brain Capillaries

Abstract: Breast cancer resistance protein (BCRP) functions as a major molecular gatekeeper at the blood-brain barrier. Considering its impact on access to the brain by therapeutic drugs and harmful xenobiotics, it is of particular interest to elucidate the mechanisms of its regulation. Excessive glutamate concentrations have been reported during epileptic seizures or as a consequence of different brain insults including brain ischemia. Previously, we have demonstrated that glutamate can trigger an induction of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
18
1
Order By: Relevance
“…It is also possible that the activity of COX‐2—not its expression—is what correlates with P‐gp expression. This could also explain why we observed no relationship between COX‐2 and BCRP expression, in contrast to previous findings from Salvamoser and colleagues …”
Section: Discussioncontrasting
confidence: 99%
“…It is also possible that the activity of COX‐2—not its expression—is what correlates with P‐gp expression. This could also explain why we observed no relationship between COX‐2 and BCRP expression, in contrast to previous findings from Salvamoser and colleagues …”
Section: Discussioncontrasting
confidence: 99%
“…These authors provided evidence for the contribution of NMDA/COX-2 cascade to the down regulation of BCRP expression and activity in porcine capillaries. Moreover, using human capillaries isolated from surgical specimens of epilepsy patients, they were able to confirm a glutamate-induced down-regulation of BCRP expression and activity in human capillaries, which argued against major species differences (Salvamoser et al, 2015). In similar study, the same group showed that MRP2 expression and activity increased significantly in porcine and human BBB models after exposure to glutamate.…”
Section: Introductionmentioning
confidence: 93%
“…While Yousif et al showed a significant increase in BCRP expression at rat BBB mediated by NMDA/COX-2 cascade (Yousif et al, 2012), a recent report by Salvamoser et al showed that glutamate exposure decreased BCRP expression and activity in isolated porcine capillaries (Salvamoser et al, 2015). These authors provided evidence for the contribution of NMDA/COX-2 cascade to the down regulation of BCRP expression and activity in porcine capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence from in vitro and in vivo rodent studies suggests that targeting this pathway could control P-gp expression and activity levels, and thus, help increase ASD brain penetration and improve ASD efficacy to control seizures in drug-resistant epilepsy (131, 137139). One study of Salvamoser et al (140) showed that exposing isolated porcine brain capillaries and human brain capillaries from ASD-resistant patients with FCD to glutamate resulted in reduced BCRP protein expression levels. This finding is in contrast with data from human studies comparing BCRP expression between control and epileptic human brain tissue (89, 90, 92, 95), and unpublished data from our lab clearly demonstrate seizure-induced upregulation of BCRP protein expression and activity levels in brain capillaries from chronic epileptic rats.…”
Section: Potential Mechanisms Of Asd Resistancementioning
confidence: 99%